Linking quality of work-life to turnover intention: The role of organizational citizenship behavior - Robertus M. B. Gunawan; Widodo Widodo (Jurnal Konseling dan Pendidikan, 2021)
Turnover is an enemy of the organization that needs to be avoided by every organization, including private school organizations. Hence, this study aims to examine the effect of quality of work-life (QWL) on teachers' turnover intention, mediated by organizational citizenship behavior (OCB), to overcome turnover intention among private school teachers. This research uses a quantitative approach. A questionnaire was collected the data through the survey methods for 224 teachers of an honorary private school in Indonesia. Data analysis uses path analysis supported by descriptive statistics and correlational. The results indicated that QWL affects teachers' turnover intention through QWL. Therefore, the teachers' turnover intention can reduce by improving QWL and OCB. This finding can be discussed as a reference among researchers and practitioners to develop better models of teachers' turnover intention in various contexts in the future.